The Role of Parents and Teachers In Maintaining Oral Health With Dental Caries in Children With Down Syndrome - Mira Indah Pusponegoro; Ratih Larasati; Agus Marjianto; Anshad Ansari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Down syndrome it is also called trisomy 21 because it has three chromosomes on chromosome 21, whereas normal people only have two. This occurs because chromosome 21 cannot separate during the cell division process, resulting in individuals with 47 chromosomes. The physical and psychological limitations experienced by children with down syndrome cause a lower ability to maintain oral and dental health and result in a higher risk of dental caries compared to normal children. Several recent studies explain that the role of parents and teachers is needed to improve oral health maintenance in order to reduce the risk of dental caries in children with down syndrome. This research aims to determine the relationship between the role of parents and teachers in keeping oral health and dental caries in children with down syndrome in the North and East Surabaya areas. This type of research is a cross sectional analytical research with 37 down syndrome children, parents and teachers as respondents. The data collection instruments used were questionnaire sheets and DMF-T examination sheets. The technical data analysis uses the Spearman rank test and multiple regression. The results of the research show that there is a significant relationship between the role of parents and teachers in maintaining oral health and dental caries in children with down syndrome. Conclusion: More active role of parents and teachers is needed in reducing the rate of dental caries in children with down syndrome.